Предмет: Математика,
автор: Аноним
Срочно, даю 98 баллов
Приложения:
![](https://files.topotvet.com/i/664/664bf708e8e871d3d625fb9909b9eaca.jpg)
Ответы
Автор ответа:
0
(х^8)'=8•х^7
(х^-11)'=(-11)•х^(-12)
(х²/³)'=2/3•х^(-1/3)
(х^(-4/5))'=-4/5•х^(-9/5)
(1/х¹°)'=-10•х^(-11)
((1-3х)⁴)'=4•(1-3х)³•(1-3х)'=-12(1-3х)³
((4х-3)^(-6))'=(-6)•(4х-3)^(-7)•(4х-3)'=-24(4х-3)^7
(1/⁴√(х/2-3)³)'=-3/4•(х/2-3)^(-1/4)•(х/2-3)'=
-3/8•(х/2-3)^(-4)
(х^-11)'=(-11)•х^(-12)
(х²/³)'=2/3•х^(-1/3)
(х^(-4/5))'=-4/5•х^(-9/5)
(1/х¹°)'=-10•х^(-11)
((1-3х)⁴)'=4•(1-3х)³•(1-3х)'=-12(1-3х)³
((4х-3)^(-6))'=(-6)•(4х-3)^(-7)•(4х-3)'=-24(4х-3)^7
(1/⁴√(х/2-3)³)'=-3/4•(х/2-3)^(-1/4)•(х/2-3)'=
-3/8•(х/2-3)^(-4)
Похожие вопросы
Предмет: Химия,
автор: stasyyyy94
Предмет: Биология,
автор: Аноним
Предмет: Українська мова,
автор: vladislavsimonenko83
Предмет: Математика,
автор: galchonok1512
Предмет: Литература,
автор: карина882